Villains or heroes?: farmers' adjustments to water scarcity - Molle, Francois; Venot, Jean-Philippe; Lannerstad, Mats; Hoogesteger, J. (Wiley, 2010)
Although farmers are often seen as wasting water and getting a disproportionate share of water, irrigation is losing out in the competition for water with other sectors. In cases of drought, water restrictions are overwhelmingly imposed on irrigation while other activities and domestic supply are only affected in cases of very severe shortage. All over the world, farmers have been responding to the challenge posed by both short- and long-term declining water allocations in many creative ways, but these responses have often been overlooked by policy makers. This paper examines how farmers have adapted to water scarcity in six different river basins of Asia and the Middle East. It inventories the different types of adjustments observed and shows not only their effectiveness in offsetting the drop in supply but also their costs to farmers and to the environment and their contribution to basin closure. The conclusion calls for a better recognition of the efforts made by the irrigation sector to respond to water challenges and of its implications in terms of reduced scope for efficiency gains in the irrigation sector.